To William Denny, Esquire, lieutenant governor and commander in cheif of the province of Pennsylvania, &c. : the address of the trustees and treasurer of the Friendly Association for Regaining and Preserving Peace with the Indians by Pacific Measures - Armbruster, Anthony, 1717?-1796; Sower, Christopher, 1721-1784 ([publisher not identified], 1757)
September 14, 1757 Address of the Trustees and Treasurer of the Friendly Association for Regarding and Preserving Peace with the Indians by Pacific Measures, sent to Lt. Governor William Denny. References were made to the prior governor's declaration of war against the Indians, the Treaty of Easton, as well as other relevant events.